Municipal solid waste management in Kolkata, India – A review - Chattopadhyay, Subhasish; Dutta, Amit; Ray, Subhabrata (Waste management (Elmsford), 2009)
Kolkata is one of four metropolitan cities in India. With an area of 187.33 sq km and a population of about 8 million, it generates around 3,000 t d −1 of municipal solid waste (MSW) at a rate of 450–500 g per capita per day. With rapid urbanization as a result of planned and unplanned growth and industrialization, the problems associated with handling MSW have increased at an alarming rate over the past few years. No source segregation arrangement exists; there is only limited (60%) house-to-house collection; and 50–55% open vats are used in the present collection system. The operational efficiency of the Kolkata Municipal Corporation (KMC) transport system is about 50%, with a fleet composed of about 30–35% old vehicles. The majority (80%) of these, particularly the hired vehicles, are more than 20 years old. The newly added areas covered by KMC have even lower collection efficiencies, and only an informal recycling system exists. The waste collected has a low energy value (3,350–4,200 kJ kg −1) with high moisture and inert content. A 700 t d −1 compost plant set up in 2000 has not been functioning effectively since 2003. Open dumping (without liners and without a leachate management facility) and the threat of groundwater pollution, as well as saturation of an existing landfill site (Dhapa) are the most pressing problems for the city today. KMC spends 70–75% of its total expenditures on collection of solid waste, 25–30% on transportation, and less than 5% on final disposal arrangements. The Kolkata Environmental Improvement Project, funded by the Asian Development Bank, is seen as only a partial solution to the problem. A detailed plan should emphasize segregation at the source, investment in disposal arrangements (including the use of liners and leachate collection), and an optimized transport arrangement, among improvements.